Terrorist Attacks and Financial Markets - Bas Bonekamp; Tom van Veen (Center for Economic Studies and ifo Institute (CESifo), 2017)
This paper investigates the magnitude and the duration of the effect of a terrorist attack on stock market indices. We investigate the impact of New York (2001), Madrid (2004), London (2005), Boston (2013), Paris (2015), Brussels (2016), Nice (2016) and Berlin(2016) on the stock indices of the USA (S&P), Japan (NIKKEI), Germany (DAX), Spain (IBEX), UK (FTSE), France (CAC) and the Euronext Index (BEL). We use both a graphical analysis and an event study methodology to assess the effect of terrorist attacks on stock market indices. We conclude that both the magnitude and the duration of the effect are moderate and have diminished over the years.
Keywords: G10; G14; G15; 330; terrorist attacks; event studies; stock market indices